(3Gdbhi GdWHjYjIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje ; Efg bO cGf jbY EdjfG cJH HYedgG GdTjN CHh GdaQL GHf GdWjH ai GdWH s
(3BNQgG (B:s
(3Cf GdMGQ jDGNP HShA eRGL LGQg , hHCde LGQg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B812 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B147 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(4829(11)) s
Keywords: (3GdWHs